Implementation of Discovery Learning Models to Improve Students Mathematic Learning Outcomes - Erina Ika Muhayati; Wulan Trisnawaty; Subaidah Subaidah (Jurnal Penelitian Pendidikan IPA, 2023)
The aims of this research was describing about implementation of discovery learning model to increase students mathematics learning outcomes. It was a quantitative research with one shot case study design. Subjects of this research were students of Xth TEI 1 SMK Negeri 1 Driyorejo for the academic year 2021/2022. Data collection technique using three essay questions with data analyze technique include validity test and completeness test of Minimum Completeness Criteria. In this research, students are given 6 steps of discovery learning. There are stimulation, problem statement, data collection, data processing, verification, and generalization. The research revealed that students learning outcome using discovery learning having increase from 30 to 89. It could be conclude that discovery learning model can improve students' mathematics learning outcomes.